Performance study of MATLAB modelled PV panel and conventional PV panel interfaced with LabVIEW - K, Jaiganesh; N, Karuppiah; S, Ravivarman; Asif, Md (International Journal of Engineering and Technology, 2018)
The maximum electrical energy conversion efficiency of the Solar PV panel is up to 22% in normal conventional roof- top system under the temperature of 25ËšC on Standard Test Condition (STC). In Indian climatic conditions, the atmospheric temperature is mostly above 35ËšC to 45ËšC, it incites 35ËšC to 80ËšC temperature on the PV panel. The black body of the PV panel absorbs more heat. This temperature affects the electrical efficiency of the panel significantly. This paper proposes the mathematical modelling of the solar PV panel for different solar irradiation and the temperature. The experimental evaluation is conducted in the latitude of 11.36 (N) and longitude 77.82 (E). The testing and monitoring was done with LabVIEW based National Instruments hardware such as NI cDAQ-9178, NI DAQ - 9227 and NI DAQ 9225. The comparative study between the simulated result and real time hardware results are discussed in this paper. The test result shows that the output of the proposed model mismatches with the experimental output of the solar PV panel due to the negative correlation between the efficiency and temperature for variable irradiation condition. It shows a power difference of 9.41W between the output of the proposed model and the experimental setup.Â Â